Contrıbutıng Factor To Incıdent Of Patıent Safety When Implementıng Patıent Safety Goal On Inpatıent Rsds Hospıtal Jakarta Indonesıa - Desak Nyoman Sithi (International Journal of Advanced Science and Technology, 2020)
Integrated circuits are in demand to be invetigated for its economical performance. Therefore, it is vialbe to experiment on ternary based operations[7]. A ternary half adder based on ternary multiplexer and logic primitives is proposed and its performance is analyzed in detail. This proposed ternary half is sensibly designed with the simplified expressions using the ternary k-map. The combinational logic blocks for the SUM and CARRY are designed, verified, constructed and simulated with Tanner EDA (130nm) at 1.2 V. Background: Unsafe nursing care is a significant source of incident of patient safety, with unawareness by them self.  53.3% of nurses had experience to conduct a patient safety incident. The purposed of this study is to investigate “Factors Contributing to patient safety incident when implementing patient safety goals. Method: This study used descriptive and analytical design with a cross sectional approach, and concurrent mix quantitative and qualitative method by open question, to complete information is needed. The population of this research is nurses, who work on inpatient hospital setting with 104 sample sizes. The quantitative data collection analyzes by Univariate, Bivariate and Multivariate, while qualitative data, analyze by content analysis.  Result: the prevalence of incident of patient safety is too high 40.2%, while confirm by content analysis is higher, up to 46.1%. Moreover, six top contributing factors to incident of patient safety are staff factor, task factor with (PV 0.000), while work environment factor is significant with (PV 0.04), organization factor, training and education and team factor are also significant with (Pv 0.000). The most contributing factor is team factor with Wald test value of 12.935.Conclusion:  Almost all of factor (75%) are contribute to incident of patient safety, with high rate   prevalence. Factor contributing to incident of patient safety are staff factor, task factor, work environment factor, organization factor, training &education and team factor contribute to incident of patient safety. The most contributing factor is team factor with significantly of 90.6%.